Muslimske identiteter i Tromsø - Molaug, Astrid (Universitetet i Tromsø, 2009)
Muslim identities in Tromsø This thesis explores how seven Muslims in Tromsø understand different frames and conditions for their various Muslim identities. Seven interviews, analyzed and compared using Thomas A. Tweeds Crossing and Dwelling: A Theory of Religion (2006), illuminates how each orient themselves as Muslims in and according to different times and spaces. The interviews are done with Muslims born and raised in different parts of the world, but all in a society where the majority of the populations consider themselves Muslims. The problem for discussion is the following: How do seven Muslims understand different frames and conditions for their various Muslim identities in Tromsø? Questions raised are among others: What does it entail to be a Muslim in Tromsø? What happened to and how have their Muslim identities evolved, after moving from a society where they as Muslims were part of a majority, and settling in a Western society where they are part of a Muslim minority? How did these encounters change their different Muslim identities? What factors influenced the changes? What significance do the mosques have? What are their notions regarding non-Muslim Norwegians’ conceptions, and regarding the medias portrayal of Islam and Muslims? And how might all this affect their understandings about being Muslim? In other words, what does it imply to each individual to be a Muslim in Tromsø?